Abdominal trauma surgery during recent US combat operations from 2002 to 2016. Issue 1 (July 2018) - Stockinger, Zsolt T.; Turner, Caryn A.; Gurney, Jennifer M.
Abstract : BACKGROUND: Abdominal surgery constitutes approximately 13% of surgical procedures performed for combat injuries. This study examines the frequencies and type of abdominal surgical procedures performed during recent US Military operations. METHODS: A retrospective analysis of the Department of Defense Trauma Registry was performed for all Role 2 (R2) and Role 3 (R3) medical treatment facilities (MTFs), from January 2002 to May 2016. The 273 International Classification of Diseases, Ninth Revision, Clinical Modification procedure codes that were identified as abdominal surgical procedures were stratified into 24 groups based on anatomic and functional classifications and then grouped by whether they were laparoscopic. Procedure grouping and categorization were determined, and adjudicated if necessary, by subject matter experts. Data analysis used Stata version 14 (College Station, TX). RESULTS: A total of 26, 548 abdominal surgical procedures were identified at R2 and R3 MTFs. The majority of abdominal surgical procedures were reported at R3 facilities. The largest procedure group at both R2 and R3 MTFs were procedures involving the bowel. There were 18 laparoscopic procedures reported (R2: 4 procedures, R3: 14 procedures). Laparotomy not otherwise specified was the second largest procedure group at both R2 (1, 060 [24.55%]) and R3 (4, 935 [22.2%]) MTFs. Abdominal caseload was variable over the 15-year study period. CONCLUSIONS: Surgical skills such as open laparotomy and procedures involving the bowel are crucial in war surgery. The abundance of laparotomy not otherwise specified may reflect inadequate documentation, or the plethora of second- and third-look operations and washouts performed for complex abdominal injuries. Traditional elective general surgical cases (gallbladder, hernia) were relatively infrequent. Laparoscopy was almost nonexistent. Open abdominal surgical skills therefore remain a necessity for the deployed US Military General Surgeons; this is at odds with the shifting paradigm from open to laparoscopic skills in stateside civilian and military hospitals. LEVEL OF EVIDENCE: Epidemiologic study, level III.